Opportunistic Infections Are More Prevalent in Crohn's Disease and Ulcerative Colitis: A Large Population-Based Study. Issue 2 (17th July 2019) - Sheriff, Mohammed Zaahid; Mansoor, Emad; Luther, Jay; Ananthakrishnan, Ashwin N; Abou Saleh, Mohannad; Ho, Edith; Briggs, Farren B S; Dave, Maneesh
Abstract : Our study demonstrates significantly higher rates of bacterial, fungal and viral infections in IBD patients when compared to the controls without IBD. Overall, viral infections were numerically more common, whereas bacterial infections had the highest risk in IBD patients. Abstract: Background: Opportunistic infections (OIs) are more common in patients with inflammatory bowel disease (IBD); however, there have been limited large-scale studies of OIs in IBD. We investigated the epidemiological characteristics of OI in Crohn's disease (CD) and ulcerative colitis (UC) using a large population-based database. Methods: Data were collected from a commercial database (Explorys Inc., Cleveland, OH, USA) that provided electronic health records from 26 major integrated US health care systems from 1999 to March 2018. In this data set, we identified all CD and UC patients, based on Systemized Nomenclature of Medicine–Clinical Terms. Within these cohorts, we identified a variety of OIs and compared the prevalence rate of OI in individuals with IBD with that of controls (patients in the database between March 2013 and March 2018 without the diagnosis of IBD). Results: Explorys included 153, 290 patients with CD and 128, 540 patients with UC between March 2013 and March 2018. The prevalence of OIs was 17.8% in CD, 19.2% in UC, and 7% in non-IBD controls. When compared with non-IBD controls, all OIs were more common in CD (prevalence ratio [PR], 2.54; 95% confidence interval [CI], 2.51–2.57) and UC (PR, 2.74; 95% CI, 2.71–2.77). Overall, viral infections were numerically more common, whereas bacterial infections had the highest PRs in CD and UC when compared with controls without IBD. Conclusions: We found significantly higher rates of OI in IBD. Our study suggests the need for close follow-up of IBD patients to diagnose and provide vaccinations where applicable for prevention of infections.